A novel self-assembled pH-sensitive targeted nanoparticle platform based on antibody–4arm-polyethylene glycol–pterostilbene conjugates for co-delivery of anticancer drugs. Issue 4 (12th January 2018) - Liu, Ke-Feng; Liu, Yan-Xue; Dai, Lin; Li, Chun-Xiao; Wang, Luying; Liu, Jing; Lei, Jian-Du
Abstract : Recently, antibody–drug conjugates (ADC) have shown potential for cancer immunotherapy by tumor-targeted delivery of anticancer drugs. Abstract : Recently, antibody–drug conjugates (ADC) have shown potential for cancer immunotherapy by tumor-targeted delivery of anticancer drugs. However, the development of ADC is subject to many restrictions, such as the payloads, stabilities and intracellular uptake of the drugs, which has greatly restricted their clinical application. To overcome these hurdles, in this study, a novel pH-sensitive targeted nanoparticle platform based on a newly synthesized amphipathic antibody–drug conjugate (antibody–4arm-polyethylene glycol–pterostilbene, mAb–4arm-PEG–PS) was fabricated for co-delivery of another anticancer drug (10-hydroxy camptothecin, HCPT). The prepared mAb–4arm-PEG–PS/HCPT nanoparticles (NPs) had a moderate particle size (∼120 nm), a high drug to antibody ratio (∼22.4) and relatively high binary drug loading capacity (∼24.2 wt% HCPT, ∼2.9 wt% PS). Moreover, the mAb–4arm-PEG–PS/HCPT NPs exhibited enhanced intracellular uptake (∼5 fold that of mAb–4arm-PEG–PS conjugates) and excellent cytotoxicity in vitro . In subsequent Daudi lymphoma xenograft assays, compared with free drugs and mAb–4arm-PEG–PS conjugates, the mAb–4arm-PEG–PS/HCPT NPs inhibited tumor growth more efficiently. Our results indicated the great potential of mAb–4arm-PEG–PS/HCPT NPs for targeted co-delivery of anticancer drugs to solid tumors.